ANALISIS WAKTU KELULUSAN MAHASISWA FMIPA UNIVERSITAS UDAYANA DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - SRINADI, I GUSTI AYU MADE; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 9 No 3 (2020), 2020)
The graduate profile shows the competencies of the graduate. Not all students are able to complete their studies within the specified study period. Some students are threatened with dropping out (DO) because within the maximum time limit given, which is 7 years for undergraduate degrees, they are still unable to complete their studies. This condition has a negative impact on student graduation on time which negatively affects to the assessment of study program accreditation. To anticipate this condition, it is necessary to know what obstacles students made they are unable to complete their studies on time. The information obtained can be used as a guide in anticipating no more students exceeds study period. The purpose of this study was to determine the graduation of undergraduate students of FMIPA Udayana University and the factors that influence student graduation. The research sample was taken using purposive sampling technique of FMIPA, Udayana University graduation period January 2002 to January 2019. Data analysis used statistics descriptive and exploratory factor analysis. The graduation data of FMIPA undergraduate students, there was 2710 students, 2190 (81%) was able to complete studies no more than five years and 514 students (19%) more than five years. There is significant dependency between study period with gender and study program. There are two intellectual factors that influence student graduation not on time, namely the knowledge and skills factor with an explainable diversity of 63.2%.